2018
DOI: 10.3168/jds.2017-14279
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effect of 3 phytoceutical products on elimination of bacteria in experimentally induced Streptococcus uberis clinical mastitis

Abstract: Our objective was to assess the ability of 3 herbal products to eliminate experimentally induced Streptococcus uberis mastitis. These herbal products, also known as phytoceuticals, are used in organically managed dairy cattle to maintain or promote udder health. The products tested were an intramammary product, a topical product, and a product applied to the vulvar area. These products are not approved by the US Food and Drug Administration for treatment of mastitis but they are sold to enhance milk quality or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…36 However, adult dairy cattle supplemented with EO products containing either garlic, thyme, or oregano failed to cure experimentally induced Streptococcus uberis mastitis following either topical or intramammary administration. 43 Oregano supplementation also failed to reduce Eimeria oocyst shedding in dairy heifers. 37 Garlic (Allium sativum) and garlic oils have the capacity to eliminate free radical species and reduce lipid peroxidation in vivo.…”
Section: Nutraceuticalsmentioning
confidence: 97%
“…36 However, adult dairy cattle supplemented with EO products containing either garlic, thyme, or oregano failed to cure experimentally induced Streptococcus uberis mastitis following either topical or intramammary administration. 43 Oregano supplementation also failed to reduce Eimeria oocyst shedding in dairy heifers. 37 Garlic (Allium sativum) and garlic oils have the capacity to eliminate free radical species and reduce lipid peroxidation in vivo.…”
Section: Nutraceuticalsmentioning
confidence: 97%
“…Studies have suggested that garlic, thymol, and carvacrol could assist in controlling S. uberis-induced mastitis. However, bacterial cures were not consistently achieved, and it was recommended that organic herds using these products observe a withholding time of at least 24 hours (Mullen et al, 2018). Herbal products such as Phyto-Mast and Cinnatube have been shown to be comparably effective to conventional therapies, without causing adverse effects on cows (Mullen et al, 2014).…”
Section: Organic Farming and Udder Healthmentioning
confidence: 99%
“…However, farmers have reported drying off the affected quarter, or—in severe cases—culling the animal as opposed to using alternatives to antimicrobials [ 100 ]. Mullen [ 101 ] evaluated the pharmacokinetics of garlic, thymol and carvacrol for use in controlling S. uberis -induced mastitis and reported that withhold times of at least 24 h should be established in organic herds that use these products. However, these products did not produce bacterial cures for mastitis [ 101 ].…”
Section: Managing Transition Organic Dairy Heifer Behaviors and Udder...mentioning
confidence: 99%
“…Mullen [ 101 ] evaluated the pharmacokinetics of garlic, thymol and carvacrol for use in controlling S. uberis -induced mastitis and reported that withhold times of at least 24 h should be established in organic herds that use these products. However, these products did not produce bacterial cures for mastitis [ 101 ]. Furthermore, researchers reported the efficacy of the herbal products (Phyto-Mast and Cinnatube) was similar to conventional therapies, and the products did not have any adverse effects on cows [ 102 ] Frequent stripping or the use of a topical udder rub are commonly used on organic farms [ 5 ].…”
Section: Managing Transition Organic Dairy Heifer Behaviors and Udder...mentioning
confidence: 99%